Pengembangan Aplikasi Web Google Script sebagai Instrumen Assesment - Eri Teguh Kurniawan Suyatna (Jurnal Didaktika Pendidikan Dasar, 2022)
This research on the development of the ADDIE model uses the google apps script as an assessment instrument for learning science in grade 9 for online Reproductive System material. The limitations of features on Google Forms such as the absence of a timer, idle time and active tab checking on the browser used by students make the author want to add these features. Prior to testing, the content of the items was validated by experts and the results were all 100% valid. After the judgment of the experts about the application, namely in the category of conformity with the curriculum, a percentage of 100% was obtained. The steps for implementing the online quiz instrument are easily understood by students who are new to this application, obtaining a score of 97,5%. The ease with which students use this media obtains a percentage of 82,5%. The feasibility of the development results when applied in schools obtains a percentage of 85%. The practicality test results are (a) 82,5% for ease of application, (b) 78,75% for the navigation category, (c) 78,75% for menus, and (d) 83,13% for application excellence rating.